Physiological profile of water polo players in different competitive levels - Melchiorri, G.; Padua, E.; Sardella, F.; Manzi, V.; Tancredi, V.; Bonifazi, M. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The purpose of this study was to determine if there are different physiological characteristics in water polo players of three different competitive levels (national team, NT, junior national team, NJ, and amateur club, AC). METHODS: To better define the training levels of water polo players competing at different levels, we administered a shuttle swim test (SST, a specific test used by Italian coaches) and a classic speed-lactate test. The shuttle swim test is based on actions at maximum intensity followed by incomplete recoveries. To compare the athletes, we used their morphological characteristics, the speed during an incremental test associated with fixed blood lactate concentrations of 2 mmol/l (Aerobic Threshold, AT) and 4 mmol/l (Anaerobic Threshold, AnT), and the SST data (speed, heart rate and lactate concentration). RESULTS: The heart rate at the end of the SST was 164±12 beats/min for NT, 166±10 beats/min for NJ (no significant difference, P>0.05) and 179±9 beats.min-1 for AC (significantly different from NT and NJ, P<0.05). The AT and AnT speeds were significantly higher in NT than in AC and NJ (P<0.05). No significant differences were found in AT and AnT speeds between AC and NJ (P>0.05). The mean speed during the shuttle swim test was significantly higher in NT and NJ than in AC (P<0.05). Lactate values were similar in the NT, AC and NJ groups (P>0.05). The SST mean speed was significantly correlated with the AT (P<0.01) and AnT speeds (P<0.05) in three groups. In all groups no significant correlation was found between SST blood lactate and AT or AnT speeds (P>0.05). CONCLUSION: Some differences were found among the senior and junior professional and amateur water polo players in both SST performance and Aerobic and Anaerobic Thre-shold speeds. The shuttle swim test for water polo provides conditioning coaches and sport scientists with data on the sport-specific movement speed and the competition-specific fatigue resistance in each athlete.